(untitled) (Baghdad Science Journal, 2025)
This study has been performed on the vegetative parts of the local Horsetail Equisetum arvense L.,which grow naturally in Haj Umran , north of Iraq , included some heamatological tests coccerning blood coagulation by using different concentration of both water and ethanolic extracts in vitro and in vivo . The results revealed that water extract of (25 and 50) mg/ml decreased clotting time in vitro, but higher concentration (100) mg/ml had reverse effect ( stoped coagulation) , Also the low concentration of crude extracts (water and ethanolic) were very efficient to decrease clotting time, and increase platelet count in vivo. But higher concentration (100) mg/ml increased the clotting time with decrease in platelet count .